2006
DOI: 10.1364/oe.14.001924
|View full text |Cite
|
Sign up to set email alerts
|

Observation of composite gap solitons in optically induced nonlinear lattices in LiNbO3:Fe crystal

Abstract: We observe experimentally, the first time to our knowledge, two types of composite gap solitons in optically induced one-dimensional nonlinear lattice in LiNbO(3) crystal. We observe the staggered bright composite gap soliton when a single Gauss probe beam is incident at Bragg angle as well as a dipole probe beam is incident at normal incidence. When a single Gauss beam is at normal incidence, the in-phase bright composite gap solitons are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…͓DOI: 10.1063/1.2793629͔ Discrete or gap solitons ͑GSs͒ have been intensively studied in one-or two-dimensional ͑2D͒ photonic lattice ͑PL͒. [1][2][3][4][5][6][7] Light propagation in the PL is mainly governed by the interplay between the tunneling between adjacent waveguides and the nonlinearity. A balance between these two effects results in self-localized states or GSs.…”
Section: Gap Solitons In Optically Induced Two-dimensional Square Phomentioning
confidence: 99%
“…͓DOI: 10.1063/1.2793629͔ Discrete or gap solitons ͑GSs͒ have been intensively studied in one-or two-dimensional ͑2D͒ photonic lattice ͑PL͒. [1][2][3][4][5][6][7] Light propagation in the PL is mainly governed by the interplay between the tunneling between adjacent waveguides and the nonlinearity. A balance between these two effects results in self-localized states or GSs.…”
Section: Gap Solitons In Optically Induced Two-dimensional Square Phomentioning
confidence: 99%
“…[ 26 ] Uniquely, for periodically poled LNO crystals, photochemical reduction can result in the formation of nanowires that form along the domain wall [ 18 ] or within domains. [31][32][33] Photorefractive ferroelectrics are known to support spatial solitons, i.e. [10][11][12][13][14][15][16][17][18][19]27 ] The photodeposition is contingent on the production and diffusion of electrons through the photogalvanic process which can only occur with super bandgap illumination energies.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent experimental studies have convincingly demonstrated the advantages of the given approach. Along with the SBN crystals, LiNbO 3 doped with some impurities (for example, Fe and Cu ions) is promising for obtaining optically-induced nonlinear waveguide structures [7][8][9]. The photorefractive optical nonlinearity of LiNbO 3 is caused by the photovoltaic effect, and its nonlinear response can be observed without application of external electric fields, as in the case of SBN.…”
Section: Introductionmentioning
confidence: 99%
“…By this method, it is possible to produce waveguide optical structures with a required topology in bulk samples and planar optical waveguides [7,8,12]. The standard holographic technology allows only harmonic modulation of the refractive index of the medium to be obtained.…”
Section: Introductionmentioning
confidence: 99%